FASILITAS PENGEMBANGAN UMKM DI BANJARBARU - Shafly, Muhammad Faris; Agusniansyah, Nursyarif Agusniansyah (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
MSMEs are one of the employment sectors that have become an important state asset with their potential as a high contributor to the country's GDP. However, in 2020, the contribution of MSMEs has decreased drastically to only 37% of each year which always contributes above 50%. This is due to the COVID-19 pandemic. Therefore it’s necessary for an MSME development facility as an effort to prepare MSME actors in the future in terms of their education and creativity in entrepreneurship to be able to adapt in crisis situations. The approach used is Architectural Programming owned by Donna P. Duerk as a direct response in solving educational, creative, collaborative problems by implementing an exploration of the needs of its development facilities with the facility exploration process using the IP2K strategy as a method assessment parameter, until finally obtaining the concept of programming results. With this facility, it is hoped that MSMEs will become a source of economy that is not easily broken.